Working with Musically Gifted Students - Stopar, Anja (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter focuses on the identification and development of musically gifted students, emphasizing the importance of tailored teaching approaches for their progress. It examines the characteristics of musical giftedness, the identification process, and the role of teachers and parents in nurturing these students' potential. Individualized support enhances their motivation, musical expression, and academic achievement. Examples of personalized approaches, such as differentiated tasks, enrichment programs, and mentorship, are provided, alongside the integration of quality musical activities, including improvisation, creative singing, and musical games. The chapter also addresses the risks of overburdening students, emphasizing the importance of a balanced approach that respects their personal boundaries. A systematic approach to educating musically gifted students fosters the development of their creative and intellectual potential, contributing to their holistic personal growth.